Last Battle, the (The Chronicles of Narnia, Book 7) - Lewis, C. S. (HarperCollins Publishers London, 2009)
Illustrations in this ebook appear in vibrant full colour on a full colour ebook device, and in rich black and white on all other devices. Narnia ... where lies breed fear ... where loyalty is tested ... where all hope seems lost. During the last days of Narnia, the land faces its fiercest challenge-not an invader from without but an enemy from within. Lies and treachery have taken root, and only the king and a small band of loyal followers can prevent the destruction of all they hold dear in this, the magnificent ending to The Chronicles of Narnia. The Last Battle is the seventh and final book in C.S. Lewis's The Chronicles of Narnia, a series that has become part of the canon of classic literature, drawing readers of all ages into a magical land with unforgettable characters for over fifty years. A complete stand alone read, but if you want to relive the adventures and find out how it began, pick up The Magician's Nephew, the first book in The Chronicles of Narnia